Redox‐Controlled Selectivity of CH Activation in the Oxidative Cross‐Coupling of Arenes1. Issue 6 (23rd December 2012) - Cambeiro, Xacobe C.; Boorman, Tanya C.; Lu, Pengfei; Larrosa, Igor
<x xml:space="preserve">Abstract</x> Gold brings us together: Taking advantage of the orthogonal reactivities of AuI and AuIII towards CH activation of electron‐poor and electron‐rich arenes, respectively, a novel approach for the synthesis of biaryls through double CH activation is proposed. Stoichiometric studies demonstrate that these oxidative couplings occur with high selectivity at low temperature.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>